2000
DOI: 10.1042/bj3460603
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression, synthesis and secretion of a novel fibrinogen/angiopoietin-related protein that prevents endothelial-cell apoptosis

Abstract: Using degenerate PCR we isolated a cDNA encoding a novel 406- and 410-amino acid protein from human and mouse embryonic cDNAs and have designated it 'hepatic fibrinogen/angiopoietin-related protein' (HFARP). The N-terminal and C-terminal portions of HFARP contain the characteristic coiled-coil domains and fibrinogen-like domains that are conserved in angiopoietins. In human and mouse tissues, HFARP mRNA is specifically expressed in the liver. HFARP mRNA and protein are mainly present in the hepatocytes. HFARP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
150
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(152 citation statements)
references
References 24 publications
1
150
0
1
Order By: Relevance
“…It is noteworthy that the proband, when treated with pharmacological doses of www.cell-research.com | Cell Research Silvia I Anghel and Walter Wahli 501 npg rosiglitazone, in combination with metformin, had a good glycemic control [193]. Another well-studied variant is the PPARg 2 P12A [70,73,194,195]. This is the only well-described change found so far in the N-terminal domain of PPARg 2 .…”
Section: Pparg Loss Of Function Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that the proband, when treated with pharmacological doses of www.cell-research.com | Cell Research Silvia I Anghel and Walter Wahli 501 npg rosiglitazone, in combination with metformin, had a good glycemic control [193]. Another well-studied variant is the PPARg 2 P12A [70,73,194,195]. This is the only well-described change found so far in the N-terminal domain of PPARg 2 .…”
Section: Pparg Loss Of Function Mutationsmentioning
confidence: 99%
“…This is the only well-described change found so far in the N-terminal domain of PPARg 2 . The initial study of Finnish and second-generation Japanese populations concluded that the less common 12A allele promotes insulin sensitivity and confers protection against type 2 diabetes [70,73,194,195]. In vitro studies showed that this allele reduces PPARg DNA binding affinity and transcriptional activity [70,73,194,195].…”
Section: Pparg Loss Of Function Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiopoietin-like proteins [ANGPTLs] or 'angiopoietinrelated proteins' [ARPs] are orphan ligands with a degree of similarity to angiopoietins: they contain a coiled-coil domain and a fibrinogen-like domain, and have angiogenic effects [1][2][3][4][5][6][7][8][9][10]. The ANGPTL family has seven members (ANGPTL 1-7), which have been found in both humans and mice [11] (except for ANGPTL5, identified only in humans [12]).…”
Section: Introductionmentioning
confidence: 99%